Structural studies on the reaction of isopenicillin N synthase with the substrate analogue delta-(l-alpha-aminoadipoyl)-l-cysteinyl-d-alpha-aminobutyrate. - Long, A; Clifton, I; Roach, P; Baldwin, J; Schofield, C; Rutledge, P (2003)
Isopenicillin N synthase (IPNS) is a non-haem iron(II) oxidase which catalyses the biosynthesis of isopenicillin N from the tripeptide delta-(L-alpha-aminoadipoyl)-L-cysteinyl-D-valine (ACV). Herein we report crystallographic studies to investigate the reaction of IPNS with the truncated substrate analogue delta-(L-alpha-aminoadipoyl)-L-cysteinyl-D-alpha-aminobutyrate (ACAb). It has been reported previously that this analogue gives rise to three beta-lactam products when incubated with IPNS: two methyl penams and a cepham. Crystal structures of the IPNS-Fe(II)-ACAb and IPNS-Fe(II)-ACAb-NO complexes have now been solved and are reported herein. These structures and modelling studies based on them shed light on the diminished product selectivity shown by IPNS in its reaction with ACAb and further rationalize the presence of certain key residues at the IPNS active site.